Dairy Foods: A Matrix for Human Health and Precision Nutrition—The impact of the dairy food matrix on digestion and absorption - David W. Everett (Journal of Dairy Science)
ABSTRACT: The nutritional value of any food product has historically been measured by the calorific value of individual components, harking back to the days of the development of the bomb calorimeter. A fuller understanding of nutrition later took into account the need for specific components, such as proteins, carbohydrates, vitamins and minerals, that are known to be required for good human health and growth. In milk and milk products, these include casein and whey proteins, lactose, milk fat triacylglycerides, minor lipid components (both charged and neutral), calcium, and micronutrients. Whey proteins are known to be richer in EAA, compared with casein, and also to contain branched chain amino acids for muscle growth. Calcium is found in the form of the calcium phosphate mineral and is dispersed, but largely insoluble, in milk. All of this information does not take into account interactions between milk components, and therefore can be considered as a reductionist nutritional approach. This review takes a structural and physical chemical approach to understand how digestibility and nutritional delivery is affected by microstructures and nutrient component interactions, with a focus on mechanistic explanations.